Construction of a Hybrid Plasmid Molecule Containing the Total Coding Region of Semliki Forest Virus 26S mRNA - Kondor-Koch, Claudia; Garoff, Henrik (Journal of General Virology, 1982)
SUMMARY We have constructed a hybrid plasmid molecule that contains the complete coding sequences from the 26S mRNA of Semliki Forest virus. Five fragments which together covered the mRNA sequence were isolated from three original hybrid plasmids and joined together at five different restriction endonuclease cleavage sites using T4 DNA ligase.
Keywords: cDNA cloning